Against Expectation: A Short Sequence With High Signal Elucidates Cone Snail Phylogeny - Kraus, Nicole J. (2010)
A short (259 nucleotide) conserved intronic sequence (CIS) is surprisingly informative for delineating deep phylogenetic relationships in cone snails. Conus species previously have been assigned to clades based on the evidence from mitochondrial 12S and 16S rRNA gene sequences (1129 bp). Despite their length, these genes lack the phylogenetic information necessary to resolve the relationships among the clades. Here we show that the relationships can be inferred from just 46 sites in the very short CIS sequence (a portion of “intron 9” of the γ-glutamyl carboxylase gene). This is counterintuitive because in short sequences sampling error (noise) often drowns out phylogenetic signal. The intron 9 CIS is rich in synapomorphies that define the divergence patterns among eight clades of worm- and fish-hunting Conus, and it contains almost no homoplasy. Parsimony, maximum-likelihood and Bayesian analyses of the combined sequences (mt rRNA + CIS) confirm most of the relationships among 23 Conus sequences. This phylogeny implies that fish-hunting behavior evolved at least twice during the history of Conus -once among New World species and independently in the Indo-Pacific clades.